2017
DOI: 10.1016/j.ctrv.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

ESR1 mutations: Moving towards guiding treatment decision-making in metastatic breast cancer patients

Abstract: Mutations in the gene coding for the estrogen receptor (ER), ESR1, have been associated with acquired endocrine resistance in patients with ER-positive metastatic breast cancer (MBC). Functional studies revealed that these ESR1 mutations lead to constitutive activity of the ER, meaning that the receptor is active in absence of its ligand estrogen, conferring resistance against several endocrine agents. While recent clinical studies reported that the occurrence of ESR1 mutations is rare in primary breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 52 publications
4
59
0
Order By: Relevance
“…One patient had co-mutations (PIK3CA mutations and AKT1 mutation). This finding agrees with previous studies in which PIK3CA mutations are particularly common, whereas AKT1 and ESR1 mutations occur less frequently in PBC patients [3][4][5]. The presence of plasma PIK3CA mutations were statistically associated with invasive lobular carcinoma (P = 0.036) and marginally associated with histological grade III carcinoma (P = 0.059) (Additional file 1: Table S3).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…One patient had co-mutations (PIK3CA mutations and AKT1 mutation). This finding agrees with previous studies in which PIK3CA mutations are particularly common, whereas AKT1 and ESR1 mutations occur less frequently in PBC patients [3][4][5]. The presence of plasma PIK3CA mutations were statistically associated with invasive lobular carcinoma (P = 0.036) and marginally associated with histological grade III carcinoma (P = 0.059) (Additional file 1: Table S3).…”
Section: Resultssupporting
confidence: 82%
“…A somatic mutation in the plekstrin homology domain of AKT1:p.Glu17Lys is found in approximately 4% of breast tumors [3]. Conversely, recent evidence describing next generation sequencing showed that another key potential mechanism of the failure of ET involves activating mutations in the ligand-binding domain of the ESR1 gene [4]. Those mutations cause ligand-independent estrogen receptor (ER) transcriptional activity that does not respond to endocrine manipulation.…”
mentioning
confidence: 99%
“…Among the patients with HER2 þ disease, HER2 alteration is the second most frequent. ESR1 mutation is another important alteration, with implications on treatment selection (37,38). It occurs in approximately 30% of patients exposed to endocrine therapies and may represent the driver of the endocrine resistance (3,9).…”
Section: Secondary Objectivesmentioning
confidence: 99%
“…Aromatase inhibitor treatment in the metastatic setting rather than in the adjuvant setting induces ESR1 mutations. 28 The pan-phosphatidylinositol 3-kinase (PI3K) inhibitor pictilisib and the CDK4/6-inhibitor palbociclib do not seem to be effective in ESR1 mutated patients, 29 and ESR1 mutations did not indicate impaired survival on fulvestrant compared to ESR1 wildtype. On examestane, however, ESR1 mutations do seem to indicate worse prognosis.…”
Section: Esr1 Mutationsmentioning
confidence: 99%